(untitled) (مجلة المنصور, 2023)
This paper demonstrates the application of genetic algorithms (GA) in array synthesis. This approach directly represents the array excitation weighting vectors as real number chromosomes. This approach has some advantages, such as giving a clearer and simpler representation of the problem, simplifying chromosome construction, and totally avoiding binary encoding and decoding so as to simplify software programming.